Mass optimisation of variable rotor speed compound split drivetrains for rotorcraft - Amri, H.; Donner, F.; Huber, F.; Weigand, M. (My University, 2019)
This publication is part of the international research project VARI-SPEED, which aims to enable rotor speed variation for a modern and ecologically efficient aviation. A mass estimation model for two different Sikorsky UH-60A drivetrain architectures was set up, calculating the mass of gears from the main-gearbox-input-shaft to the rotor-shaft and the tail-drive-shaft. One architecture includes a single compound split for transmission ratio variation, located close to the main rotor shaft. The other contains two compound splits, each located close to the turboshaft engines. Calculations were performed with different boundary conditions and the feasibility was analysed. The questions, if the compound split is the dominating factor of the mass optimisation and if the drivetrain architecture has an influence should be answered. The influence of design boundaries and the impact of the efficiency should be analysed. The compound split is not the dominating factor. Also the drivetrain architecture has an influence on the mass optimisation but not on the compound split configuration. Design boundaries have an impact, but the optimum is stable. The efficiency can have a higher impact than the mass. Variator engines have to be chosen according to the drivetrain architecture. Variation of the rotor speed via the gearbox enables the turboshaft engine, the rotor and the auxiliary units to operate at their optimal speeds. Rotor speed variation can overcome the divergent requirements between hover and fast forward flight, increase the efficiency and reduce noise and environmental impact of rotorcraft.